Visualization of gaseous iodine adsorption on single zeolitic imidazolate framework-90 particles - Yuting Lei (Nature Portfolio, 2021)
Zeolitic imidazolate frameworks are promising as high-capacity iodine adsorbents. Here the authors image the gaseous I2 adsorption on single ZIF-90 particles, clarifying the inter-particle heterogeneity in adsorption reactivity and performance improvement after introduction of linker defects .